Handbook of Consultation-Liaison Psychiatry - Leigh, Hoyle; Streltzer, Jon (Springer International Publishing : Imprint: Springer, 2015)
This updated resource refines and expands on both the core concepts and the real-world practice of consultation-liaison psychiatry in medical settings. New and revised chapters provide background and basics and describe CL psychiatry approaches to managing  a wide array of psychiatric issues in common medical conditions, including heart, lung, kidney, and liver disease, as well as delirium, dementia,  alcohol and substance use problems, and chronic pain. Besides the fine points of practice in varied chronic and acute care settings, specific patient populations such as children, elders, ob/gyn patients, the depressed, the anxious, and the immunocompromised are discussed. The latest information and insights on psychopharmacology, interviewing, and ethical and cultural issues round out the book's highly accessible coverage. A sampling of additional topics in the Handbook: Basic foundations of diagnosis, psychiatric diagnosis, and final common pathway syndromes.< An integrative care model of psychiatry in the primary care setting. Patients' personality, personality types and traits, and disorders. The chronic patient and the palliative care setting. Trauma- and stressor-related disorders. Somatic symptoms and related disorders. The Second Edition of the Handbook of Consultation-Liaison Psychiatry utilizes the new DSM-5 classification of mental disorders, and ably follows its predecessor by presenting the diverse state of the specialty to enhance the work of psychiatrists, clinical psychologists, and primary care physicians.